Wasp Venom Possesses Potential Therapeutic Effect in Experimental Models of Rheumatoid Arthritis. (6th April 2020) - Gao, Yuan; Yu, Wan-Xin; Duan, Xiao-Mei; Ni, Lian-Li; Liu, Heng; Zhao, Hai-Rong; Xiao, Huai; Zhang, Cheng-Gui; Yang, Zhi-Bin
Abstract : Rheumatoid arthritis (RA) is an autoimmune disease. Wasp venom (WV), which is considered as a traditional folk medicine in Jingpo nationality in Yunnan, China, relieves rheumatoid arthritis. The current study aimed to investigate the effect of wasp venom ameliorating rheumatoid arthritis symptoms in experimental rats. We established a model of type II collagen- (CII-) induced arthritis (CIA) in SD rats and examined the inhibition of inflammation and autoimmune response. The antiarthritic effects of WV were evaluated through the paw swelling, and histopathological score and histopathology changes of the affected paw were assessed. The anti-inflammation effects were assayed by the level of IL-6, TNF- α, IL-1 β, and the number of inflammatory cells in peripheral blood. The alteration of the T cell subset ratio in the spleen of rats was detected by flow cytometry, and at the same time, the viscera index and immune serum globulin levels were evaluated. The results suggested that various doses of WV (0.125, 0.25, and 0.5 mg/kg) significantly alleviated paw swelling and arthritis score in CIA rats with the untreated control (P < 0.05 ). WV (0.25 and 0.5 mg/kg) relieved synovial tissue lesions of ankle joints and histopathology scores of synoviocyte hyperplasia and inflammatory cell infiltration with vehicle group (P < 0.05 ). Regarding immunological regulation, 0.5 mg/kg WV lowered the immune serum globulin levels (P < 0.05 ), and we further found that WV (0.5 mg/kg) suppressed the immune response of Th cells, while enhancing the functions of Tc cells and Treg cells in spleen cells markedly (P < 0.05 ). The immunosuppressive action of WV displayed was analogous to its inhibitory effect on IL-1 β, TNF- α, IL-8, IL-6, COX-2, and PGE2 levels in rat serum. In conclusion, these findings demonstrated that WV exhibited antiarthritic activity, which might be associated with their inhibitory effects on immunoregulation and anti-inflammatory action.